Stereotactic body radiotherapy to defer systemic therapy in patients with oligorecurrent disease. (November 2022) - Willmann, Jonas; Vlaskou Badra, Eugenia; Adilovic, Selma; Christ, Sebastian M.; Ahmadsei, Maiwand; Mayinger, Michael; Guckenberger, Matthias; Andratschke, Nicolaus
Highlights: SBRT may be used to defer systemic therapy in patients with oligorecurrence. Low rates of systemic therapy after SBRT for all oligorecurrent lesions were observed. Patients had favorable OS and few treatment-related toxicities. New metastases were treated with repeat SBRT in 33.8% of patients. Fewer lines of systemic therapy and a low baseline tumor volume were associated with longer systemic therapy-free interval. Abstract: Background: Patients who develop oligorecurrent disease may be treated with metastasis-directed stereotactic body radiotherapy (SBRT) to defer the start of systemic therapy and delay its potential side effects. We report oncological outcomes and patterns of failure in patients with oligorecurrent disease treated with SBRT and determine which factors impact the interval to initiation of systemic therapy. Material/Methods: This retrospective study included patients with oligorecurrent disease (≤5 lesions) from any solid organ malignancy, treated with SBRT to all metastases and no systemic therapy for a minimum one month after SBRT between 01/2014 and 12/2019. The Kaplan-Meier method was used to analyze overall survival (OS) and progression-free survival (PFS), and the cumulative incidence of initiation of systemic therapy was analyzed assuming death without systemic therapy as a competing risk. Univariable and multivariable analyses are used to assess predictors of the systemic therapy-free interval. Results: Among 545 patients treated with SBRT for oligometastatic disease, 142 patients were treated with SBRT only for oligorecurrent disease. The most common primary tumors were lung and gastrointestinal cancer in 47 (33.1 %) and 28 (19.7 %) patients, respectively. After a median follow-up of 25 months, the median PFS and OS was 6.1 months and 48.9 months, respectively. Distant metastases were the most common first failure, and oligometastatic distant failure occured in 86 patients (60.6 %). New metastases were treated with repeat SBRT in 48 patients (33.8 %). The 1- and 2-year cumulative incidence of initiation of systemic therapy was 24.6 % and 36.8 %, respectively. In multivariable analysis, the number of previous lines of systemic therapy and the cumulative volume of metastases were significantly associated with the interval to initiation of systemic therapy. Conclusion: Selected patients with oligorecurrence achieved favorable OS and low cumulative incidence of initiation of systemic therapy. Prospective studies are warranted to determine how the deferral of systemic therapy impacts OS compared with immediate systemic therapy in combination with SBRT.